A novel preparation of GaN-ZnO2/g-C3N4 photocatalyst for methylene blue degradation - Kim Nguyen Van; Viet Nga Nguyen Thi; Thu Phuong Tran Thi; Thanh Tâm Truong; Thanh Lieu Le Thi; Ha Tran Huu; Van Thang Nguyen; Vien Vo (My University, 2021)
A novel preparation of GaN-ZnO2/g-C3N4 photocatalyst for methylene blue degradation
Keywords: GaN-ZnO2/g-C3N4; Quang xúc tác; Xử lý màu